Korelasi Keselamatan dan Kesehatan Kerja (K3) Dengan Produktivitas Kerja Karyawan (Studi Kasus: PT. Jaga Aman Sejahtera Halmahera Timur) - Ali Syahrid Naka; Amrin Sibua; Zulfikram Z (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the correlation between the K3 (Occupational Safety and Health) program and the work productivity of employees in the processing department at PT. Jaga Aman Sejahtera Halmahera Timur. The study began by finding out how the K3 program is implemented at PT. Jaga Aman Sejahtera Halmahera Timur through direct interviews, observations and several company documents. The study was conducted in the division related to the implementation of K3, namely the processing department. There are two types of data sources in this study, namely primary data and secondary data. The data obtained from the research results were processed using the Spearman Rank correlation test. The respondents selected were employees in the processing department. The sampling technique used was total sampling, which was taking samples from the entire population of employees in the processing department totaling 75 employees. The data analysis technique used descriptive analysis which was directed to explain the data in general using percentages and averages presented in table form and then interpreted and analyzed with the help of the SPSS 27.0 for Windows Software program. The results of the research data analysis showed that the correlation between Occupational Safety and Health (K3) and employee work productivity was positive, very real and strongly correlated. This can be seen from the positive correlation value of 0.743. All K3 factors have a positive, very real and strongly correlated relationship with employee work productivity. Then followed by increased K3 awareness with a correlation value of 0.744, work environment control of 0.732, safety training of 0.668, and work safety publications have the lowest correlation value of 0.639.